Renal failure requiring hemodialysis in two patients with metastatic breast cancer treated with everolimus. (May 2015) - Kuo, James C; Gorddard, Nicole; Stuart-Harris, Robin
SUMMARY : Everolimus, an mTOR inhibitor, has been shown to improve progression-free survival in patients with hormone receptor-positive metastatic breast cancer receiving exemestane, an aromatase inhibitor. Everolimus has also been found to be an effective treatment for a number of other malignancies. Renal failure in cancer patients receiving everolimus is rare. We report two cases of renal failure requiring hemodialysis in patients with hormone receptor-positive metastatic breast cancer who were receiving everolimus and exemestane.